Determinants of District/City Income Disparity in Bali Province - Muhammad Mursyid; Putu Ayu Pramitha Purwanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In regional scale of Bali Province infected symptom disparity marked income​ with Still concentrated development of the South Bali region compared to other parts of Bali. The goal study This For identify disparity income districts / cities in Bali Province 2018-2023 and analyze influence growth economy, power work, level education, allocation funds, and capital expenditures on disparity income district / city Bali Province is good in a way simultaneous and also partial. Research This use method quantitative and using secondary data obtained​ from the Central Bureau of Statistics. Data analysis techniques using Williamson index and Klassen typology as analysis disparity and continued with multiple linear regression For analyze influence growth economy, power work, level education, allocation funds, and capital expenditures on disparity income. Research results show growth economy, power work, level education, allocation funds, and capital expenditures simultaneous influential and significant to disparity income. Furthermore, growth economy, level education, allocation funds, and capital expenditures partial influential negative and significant to disparity income. Meanwhile, energy Work in a way partial influential positive and significant to disparity income. Research suggestions among other things to do equalization development for poor and depressed areas decrease, increase transportation common connecting​ all areas, development infrastructure and creation field work, availability help education and also scholarship to college tall and also postgraduate, government center still provide allocation funds especially to poor and depressed areas , and maximize potential area so that investors can invest.